Endocannabinoid metabolism inhibition has no effect on spontaneous fear recovery or extinction resistance in Lister hooded rats - Warren, William G.; Papagianni, Eleni P.; Hale, Ed; Brociek, Rebecca A.; Cassaday, Helen J.; Stevenson, Carl W. (Frontiers in Pharmacology, 2022)
Endocannabinoid transmission is emerging as a target for treating anxiety-related disorders, given its regulation of fear extinction. Boosting anandamide levels via inhibition of its metabolism by fatty acid amide hydrolase (FAAH) can enhance extinction, whereas inhibiting monoacylglycerol lipase (MAGL) to elevate 2-arachidonoylglycerol levels can impair extinction. However, whether endocannabinoids regulate fear relapse over time or extinction resistance remains unclear. In two experiments using auditory fear conditioned rats, we examined the effects of the FAAH inhibitor URB597 and the MAGL inhibitor JZL184 administered systemically on 1) spontaneous fear recovery after delayed extinction, and 2) extinction resistance resulting from immediate extinction [the immediate extinction deficit (IED)]. In Experiment 1, URB597 or JZL184 was given immediately after delayed extinction occurring 24 h after conditioning. Extinction recall and spontaneous fear recovery were tested drug-free 1 and 21 days later, respectively. We found no effects of either drug on extinction recall or spontaneous fear recovery. In Experiment 2, URB597 or JZL184 was given before immediate extinction occurring 30 min after conditioning and extinction recall was tested drug-free the next day. We also examined the effects of propranolol, a beta-adrenoceptor antagonist that can rescue the IED, as a positive control. JZL184 enhanced fear expression and impaired extinction learning but we found no lasting effects of URB597 or JZL184 on cued extinction recall. Propranolol reduced fear expression but, unexpectedly, had no enduring effect on extinction recall. The results are discussed in relation to various methodological differences between previous studies examining endocannabinoid and adrenergic regulation of fear extinction.